Germinating seed can sense low temperature for the floral transition and vernalization of winter rapeseed (Brassica rapa). (June 2021) - Liu, Zigang; Zou, Ya; Dong, Xiaoyun; Wei, Jiaping; Xu, Chunmei; Mi, Wenbo; Xu, Mingxia; Fang, Xinling; Cao, Xiaodong; Zheng, Guoqiang; Mi, Chao
Highlights: Germinating seeds can sense low temperature for completing vernalization regulated possibly by SA. The biosynthesis and signaling of SA was distinctly suppressed during vernalization in germinating seeds. The content of SA correlate with vernalization rate of germinating seeds. Abstract: The hybrid production of winter rapeseed is limited by the difficult vernalization processes. Thus, floral regulation of winter rapeseed parental lines cannot be executed through selection of sowing time during hybrid production. Therefore, in this study, strong winter rapeseed was used as the material to analyse the floral transition mechanism of germinating seed vernalization. Results demonstrated that germinating seeds could sense low temperatures and complete vernalization following a low temperature treatment for 56.5 d with a 100 % vernalization rate. The regression equation between vernalization rate (y) and vernalization treatment days (x) was determined as y = 0.019x − 0.0765 (R² = 0.8529). When the vernalization treatment time was prolonged, the vernalization rate and fruiting ability increased rapidly, and variations were observed in the membrane lipid oxidation and physiological characteristics. Furthermore, at the prolonged treatment time of 10–50 d, the salicylic acid (SA) content continued to decrease, with values significantly lower than those of the control. SA content is significantly positively correlated with the level of BrFLC transcription and a significantly negatively correlated with the vernalization rate of germinating seeds. Moreover, the expressions of genes associated with SA biosynthesis, SA signal transduction, the flowering key negative regulators were suppressed and that of positive regulators were promoted during vernalization. These results suggest that SA as a floral repressor is involved in the regulation of the vernalization process of winter rapeseed germination seeds. In addition, SA may be related to the counting dosage of vernalization.